2003
DOI: 10.1002/pssb.200309011
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen diffusion in YSZ single crystals at relatively low temperatures

Abstract: The 18O tracer experiments were carried out on two cubic YSZ single crystals at temperatures of T D = 423 K and T D = 473 K. The diffusion profiles were determined by the SIMS technique. The diffusion coefficients, the surface exchange coefficients and the activation enthalpy are discussed together with earlier data at higher temperatures. The present oxygen diffusion data demonstrate that the same diffusion process is operating over a wide temperature range.Yttria stabilized zirconia YSZ is a solid electrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
1
15
0
2
Order By: Relevance
“…The activation enthalpy for tracer diffusion calculated from our data is DH D* = (0.94 ± 0.02) eV. Combining our data with those obtained on 9.5 mol.% YSZ from Manning et al [12] and from Röwer et al [13], we obtain a global expression for the temperature range of Figure 6 shows the surface exchange coefficients k* of the single crystals YSZ as a function of inverse temperature. In general our data for pH 2 [19].…”
Section: Variation Of D* and K* With Tat Constant Ph 2 O/pomentioning
confidence: 82%
See 1 more Smart Citation
“…The activation enthalpy for tracer diffusion calculated from our data is DH D* = (0.94 ± 0.02) eV. Combining our data with those obtained on 9.5 mol.% YSZ from Manning et al [12] and from Röwer et al [13], we obtain a global expression for the temperature range of Figure 6 shows the surface exchange coefficients k* of the single crystals YSZ as a function of inverse temperature. In general our data for pH 2 [19].…”
Section: Variation Of D* and K* With Tat Constant Ph 2 O/pomentioning
confidence: 82%
“…Much effort has been devoted to characterizing bulk transport in O 2 -containing atmospheres [7][8][9][10][11][12][13], and the behavior is relatively well understood. In H 2 O-containing atmospheres YSZ is known to dissolve water according to [14] …”
Section: Introductionmentioning
confidence: 99%
“…5, while the upper limit corresponds to D chem . Figure 5 also shows the oxygen tracer diffusion data for YSZ reported by Kilo et al 11 and Rower et al 12 Of course, the lower limit of bar 2, corresponding to D T , should be used for comparison between the two sets of data (the real value of D T will be somewhere between the values represented by the limits of the bar, since the accelerating effect due to the low concentration of electronic charge carriers in YSZ is lower than that predicted by theory). As can be seen from Fig.…”
Section: Bulk Diffusionmentioning
confidence: 88%
“…It has been widely reported that impurities such as silica greatly decrease the grain-boundary conductivity in zirconia and ceria [57,61,[63][64][65][66]. Badwal and Rajendran found that the addition of only 0.2 wt.% silica was sufficient to decrease the grain-boundary conductivity of YSZ by a factor greater than 15 [65].…”
Section: Effects Of Grain Boundariesmentioning
confidence: 99%
“…Therefore, eliminating the effect of impurities on the grain boundary can benefit the ionic conductivity of the electrolyte. A number of strategies have been suggested to control the silica-rich grain boundary, including specialized heat treatments, the application of pressure, and various additives [57,61,[63][64][65][66].…”
Section: Effects Of Grain Boundariesmentioning
confidence: 99%